2016
DOI: 10.1186/s12879-016-1728-3
|View full text |Cite
|
Sign up to set email alerts
|

A decade of intestinal protozoan epidemiology among settled immigrants in Qatar

Abstract: BackgroundThe World Health Organization estimates that about 3.5 billion people worldwide are affected by intestinal parasitic infections. Reports have already emphasized the role of immigrants in outbreaks of parasitic diseases in industrialized countries. With the mass influx of immigrants to Qatar, patent intestinal parasitic infections have been observed. Herein, the prevalence of intestinal protozoan infections was analysed in 29,286 records of subjects referred for stool examination at the Hamad Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 24 publications
(40 reference statements)
2
24
3
Order By: Relevance
“…The most prevalent protozoan parasites were B. hominis among north and Saharan African subjects and G. duodenalis among western Asia subjects. In contrast to the generally falling trends in prevalence of intestinal protozoan infections among long-term residents [11], the current data revealed an increasing trend in the short-term over the period 2012–2014 among new arrivals. Comparing the current findings with the previous analysis in 2009 [8], an increase is apparent: from 3.4 to 10.9% for B. hominis among northern Africans and 1.4 to 3.6% for G. duodenalis among western Asians.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…The most prevalent protozoan parasites were B. hominis among north and Saharan African subjects and G. duodenalis among western Asia subjects. In contrast to the generally falling trends in prevalence of intestinal protozoan infections among long-term residents [11], the current data revealed an increasing trend in the short-term over the period 2012–2014 among new arrivals. Comparing the current findings with the previous analysis in 2009 [8], an increase is apparent: from 3.4 to 10.9% for B. hominis among northern Africans and 1.4 to 3.6% for G. duodenalis among western Asians.…”
Section: Discussioncontrasting
confidence: 95%
“…Giardia duodenalis was more commonly encountered among western Asians as observed in earlier work [8, 11]. Analysis of prevalence over a whole decade showed that this species declined with host age [11] but a resurgence of Giardia infection among Asian young male subjects was observed suggesting continued exposure throughout life.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations